Experiencing organ donation: feelings of relatives after consent - Marli Elisa Nascimento Fernandes; Zélia Zilda Lourenço de Camargo Bittencourt; Ilka de Fátima Santana Ferreira Boin (Universidade de São Paulo, 2015)
Objective: to identify experiences and feelings on the organ donation process, from the perspective of a relative of an organ donor in a transplant unit.Method: this was exploratory research using a qualitative approach, performed with seven family members of different organ donors, selected by a lottery. Sociodemographic data and the experiences regarding the donation process were collected through semi-structured interviews. The language material was transcribed and submitted to content analysis.Results: poor sensitivity of the medical staff communicating the relative's brain death - the potential donor - and the lack of socio-emotional support prior to the situation experienced by the family was highlighted by participants.Conclusions: the study identified the need to provide social-emotional support for families facing the experience of the organ donation process. From these findings, other care and management practices in health must be discussed to impact the strengthening of the family ties, post-donation, as well as the organ procurement indexes.